2017
DOI: 10.1038/s41598-017-12844-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mismatched and bulged nucleotides on SNP-preferential RNase H cleavage of RNA-antisense gapmer heteroduplexes

Abstract: This study focused on determining design rules for gapmer-type antisense oligonucleotides (ASOs), that can differentiate cleavability of two SNP variants of RNA in the presence of ribonuclease H based on the mismatch type and position in the heteroduplex. We describe the influence of structural motifs formed by several arrangements of multiple mismatches (various types of mismatches and their position within the ASO/target RNA duplex) on RNase H cleavage selectivity of five different SNP types. The targets wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
4
8
0
Order By: Relevance
“…ODAGal4 selectively inhibited the RNase H cleavage of mismatch RNA oligomers when using 9mer and 10mer DNAs. While there are several studies about improving mismatch discrimination using an appropriate design of oligonucleotides themselves, 7,[28][29][30] this study showed the possibility of improving mismatch discrimination by using an additive molecule. In addition, by combining this technology with a single methylphosphonate modification in a DNA strand, the range of application of ODAGal4 was extended to longer oligomers.…”
Section: Discussionmentioning
confidence: 78%
“…ODAGal4 selectively inhibited the RNase H cleavage of mismatch RNA oligomers when using 9mer and 10mer DNAs. While there are several studies about improving mismatch discrimination using an appropriate design of oligonucleotides themselves, 7,[28][29][30] this study showed the possibility of improving mismatch discrimination by using an additive molecule. In addition, by combining this technology with a single methylphosphonate modification in a DNA strand, the range of application of ODAGal4 was extended to longer oligomers.…”
Section: Discussionmentioning
confidence: 78%
“…This may be because reduction of gene expression cannot be attributed solely on the strength of complementary binding between 18-mer ASOs and each gene. This indicates that, in addition to binding affinity, the off-target effect of gapmer ASOs is also related to other factors, such as the structure of RNA around the target region [ 21 , 26 , 27 ] and the length of the gap region of ASOs [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…We envision that this could be a useful molecular biology tool for induction of RNA cleavages at precisely defined positions. Moreover, when coupled with insights about RNase H sensitivity to base mismatches [ 31 ], it may lead to the development of better SNP selective ASOs.…”
Section: Discussionmentioning
confidence: 99%